Carbon cycle perturbation and stabilization in the wake of the Triassic-Jurassic boundary mass-extinction event - van de Schootbrugge, B.; Payne, J. L.; Tomasovych, A.; Pross, J.; Fiebig, J.; Benbrahim, M.; Föllmi, Karl B.; Quan, T. M. (My University, 2008)
The Triassic-Jurassic boundary mass-extinction event (T-J; 199.6 Ma) is associated with major perturbations in the carbon cycle recorded in stable carbon isotopes. Two rapid negative isotope excursions in bulk organic carbon (δ 13Corg) occur within the immediate boundary interval at multiple locations and have been linked to the outgassing of 12C-enriched CO2 from the Central Atlantic Magmatic Province. In British Columbia, a positive δ 13Corg excursion of +5‰ (Vienna Peedee belemnite (V-PDB)) spans part or all of the subsequent Hettangian stage. Here, we examine the significance of these carbon isotope excursions as records of global carbon cycle dynamics across the T-J boundary and test the link between carbon cycle perturbation-stabilization and biotic extinction-recovery patterns. A combination of δ 13Corg and palynological analyses from the Late Triassic to Early Jurassic in the Mingolsheim core (Germany) suggests that organic carbon isotope variations are best explained as the result of both compositional changes in terrestrial versus marine input and disturbance and recovery patterns of major terrestrial plant groups across the T-J boundary. A new high-resolution δ 13Ccarb record from the Val Adrara section in the Southern Alps (Italy) spanning from the uppermost Rhaetian through Lower Sinemurian does not exhibit a negative excursion at the T-J boundary but does record a large positive δ 13Ccarb excursion of +4‰ (V-PDB) in bulk carbonate that begins at the T-J boundary and reaches a local maximum at the Early Late Hettangian boundary. Values then gradually decrease reaching +0.5‰ at the Hettangian-Sinemurian boundary and remain relatively constant into the Early Sinemurian. Complementary δ 13Ccarb data from 4 more sections that span the Hettangian-Sinemurian boundary support carbon cycle stabilization within the Upper Hettangian. Our analyses suggest that isotope changes in organic carbon reservoirs do not necessarily require a shift in the global exogenic carbon reservoir and that the positive excursion in the carbonate carbon isotope record is best explained as the combined result of an increase in atmospheric pCO2 leading to accelerated carbon cycling, decreased skeletal carbonate production, and increased organic carbon burial lasting several hundred thousand years. The termination of the positive inorganic carbon isotope excursion coincides with the recovery of marine skeletal carbonate producers and coeval changes in terrestrial vegetation and reflects the gradual reduction in pCO2 and the stabilization of the global carbon cycle during the Sinemurian.